Myristic acid beneficially modulates intervertebral disc degeneration by preventing endplate osteochondral remodeling and vertebral osteoporosis in naturally aged mice - Gong, Yan; Zhang, Yuzhuo; Chen, Xingda; Zhou, Zelin; Qin, Weicheng; Gan, Yanchi; He, Jiahui; Ma, Jizhi; Chen, Guifeng; Shang, Qi; Tang, Kai; Chen, Honglin; et al. (Frontiers in Pharmacology, 2025)
BackgroundThe origin of intervertebral disc degeneration (IDD) is highly complex, where both cartilage endplate remodeling and vertebral osteoporosis are of utmost importance. Myristic acid (MA), a saturated fatty acid derived from nutmeg, a traditional Chinese herb, has been shown to boost memory. Additionally, its isomers have been verified to have anti-osteoporotic characteristics. However, the precise mechanism by which MA functions in relation to IDD remains unclear.MethodsIn vivo, a naturally aged animal model was used. The drug—administration method of MA was intraperitoneal injection to mice aged 22 months at a dose of 2 mg/kg·d for 2 months. Micro-CT observed vertebral bone mass and endplate changes, followed by Hematoxylin‒eosin (H&E), Masson, and Safranin-O staining of tissues. TRAP staining counted osteoclasts; immunohistochemistry detected the expressions of Aggrecan and Collagen II. Bioinformatics explored MA’s anti-IDD mechanism. In vitro, MA-treated senescent endplate chondrocytes (induced by TBHP) were analyzed by RT-qPCR and immunofluorescence (IF) for senescence and matrix synthesis markers. TRAP and F-actin detected MA’s effect on RAW264.7 osteoclast differentiation (induced by RANKL); qPCR examined the expressions of osteoclast genes.ResultsUsing the naturally aged model, we found that MA tended to improve vertebral osteoporosis and endplate osteochondral remodeling, decreased the TRAP activity of the endplate, and alleviated IDD in naturally aged mice. Bioinformatics analysis suggested that the relationships among IDD, osteoporosis, and endplate degeneration were mainly linked to cellular senescence. In vitro, MA postponed the senescence of TBHP-induced endplate chondrocytes by increasing the expression of Aggrecan and decreasing the expressions of MMP-3, MMP-9, and the senescence markers p16 and p21. Additionally, MA notably inhibited osteoclast activity, as evidenced by a decrease in the number of osteoclasts and a significant suppression of F-actin formation. At the molecular level, MA efficiently reduced the expressions of osteoclast marker genes like ACP-5, CTSK, and DC-STAMP.ConclusionThe findings of this research suggest that MA is capable of inhibiting endplate osteochondral remodeling and vertebral osteoporosis, diminishing osteoclastogenesis to preserve bone mass, and consequently delaying IDD in naturally aged mice. Hence, MA holds the potential to serve as an alternative therapeutic approach for IDD.